PENGARUH LATIHAN PASSING DAN STOPPING TERHADAP KETERAMPILAN BERMAIN SEPAK BOLA SSB HARAPAN BANGSA PEKANBARU - M. Ikhsan Saputra; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: study aimed to analyze the effect of passing and stopping on the football playing skills ssb harapan bangsa pekanbaru. The design of this study uses a group of the research is wearing the approach one group pretest-posttest design. The populations in this study are 15 player. The sampling technique is to use the total sampling, where the total population is sampled. Data collection techniques were obtained from pre-test and post test. The instrument used in this study was a test of passing and stopping skills with a modified reflective board / wall. After that, the data were processed statistically, to test for normality with the Liliefors test at the significant level α (0.05). Based on statistical data analysis, it produces pre-test data Lhitung equal to 0.138, post-test data Lhitung amounting to 0.110 and Ltabel 0.220, meaning that Lhitung <Ltabel. Based on the pre-test and post-test data analysis, there is a difference in the number that increases or increases by 6. Based on the t-test analysis, it produces Tcount of 3.333 and Ttable 1.761, meaning that Tcount> Ttable. Thus , there is the effect of passing and stopping on the Football playing skills ssb harapan bangsa pekanbaru.Key Words: Passing Dan Stopping, Football